2021
DOI: 10.1002/qj.4112
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperature variability in climate models with large and small internal climate variability

Abstract: By analyzing large ensemble simulations using the Community Earth System Model (CESM_LE), the Max Planck Institute Earth System Model Grand Ensemble (MPI_GE), and Coupled Model Intercomparison Project phase 5 (CMIP5) climate models, we quantified internal climate variability (ICV) of surface temperature in each model based on the spread of simulated global mean surface temperature from the ensemble mean. Then, we examined the characteristics of simulated surface temperature variability in climate models with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This might be due to the fact that ENSO variability largely contributes to the variability of global surface temperature in the present climate (Thompson et al, 2009). Yeh et al (2021) also argued that surface temperature variability at low latitudes (30 • S−30 • N) could be considered as a key source for determining the intensity of ICV in climate models. It is found that the ENSO amplitude simulated in the Strong_ICV group either decreases (90%) or stay (10%) the same in the future out of 10-ensemble members.…”
Section: Results Enso Amplitude Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…This might be due to the fact that ENSO variability largely contributes to the variability of global surface temperature in the present climate (Thompson et al, 2009). Yeh et al (2021) also argued that surface temperature variability at low latitudes (30 • S−30 • N) could be considered as a key source for determining the intensity of ICV in climate models. It is found that the ENSO amplitude simulated in the Strong_ICV group either decreases (90%) or stay (10%) the same in the future out of 10-ensemble members.…”
Section: Results Enso Amplitude Changesmentioning
confidence: 99%
“…Note that both CESM-LENS and GFDL-LENS simulate the maximum ENSO amplitude in boreal winter (figure not shown). Following Yeh et al (2021), the ICV of global surface temperature in each member is defined as the square root of global (60 • N−60 • S, 0-360 • E) surface temperature including both land and ocean following the equation:…”
Section: Internal Climate Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…While previous studies based on the analysis of CMIP models have enhanced our understanding of internal variability (Allen et al., 2012; N. A. Davis & Birner, 2017; Grise & Davis, 2020; Grise et al., 2019; Tao et al., 2015), it is challenging to entirely disentangle the influence of external forcings from the internal variability with a limited number of realizations (Deser et al., 2020). Compared with CMIP models, a single model initial‐condition large ensemble with sufficient independent realizations is an effective tool for estimating the relative contribution of internal variability (Deser et al., 2020; Yeh et al., 2021). This occurs because, in initial‐condition large‐ensemble simulations, all the members share the same external forcing but are initiated with differing initial states (Maher et al., 2019).…”
Section: Introductionmentioning
confidence: 99%